Pengaruh Ukuran Butir Batupasir terhadap Kekuatan dan Ketahanan Batuan pada Formasi Balikpapan dan Pulau Balang - Eghi Eghi; Albertus Juvensius Pontus; Agus Winarno; Tommy Trides; Rety Winonazada (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Rock stability and service life in geotechnical and mining engineering are highly dependent on the rock's mechanical and physical parameters, where the variation in sandstone grain size is a crucial intrinsic factor. This study aims to comprehensively analyze the correlation between sandstone grain size with uniaxial compressive strength (UCS) and resistance to weathering (Slake Durability Index) in samples taken from the Balikpapan and Pulau Balang Formations in the Samarinda area, East Kalimantan. The research methodology involved a series of standard laboratory tests, including rock physical properties analysis, grain size distribution analysis, UCS testing, and slake durability testing through three cycles. The test results show a significant correlation: sandstone with finer grain sizes and higher density consistently demonstrates greater UCS values and a higher Durability Index, indicating superior mechanical and physical resistance. Specifically, the Pulau Balang Formation exhibits a more compact structure and finer grain size, resulting in better durability values compared to the Balikpapan Formation. These findings are important as a geomechanical data basis for slope design planning, rock mass stability analysis, and material selection in infrastructure projects or mining operations involving both formations.